Prune belly syndrome in surviving males can be caused by Hemizygous missense mutations in the X-linked Filamin A gene - Nida S. Iqbal; Thomas A. Jascur; Steven M. Harrison; Angelena B. Edwards; Luke T. Smith; Erin S. Choi; Michelle K. Arevalo; Catherine Chen; Shaohua Zhang; Adam J. Kern; Angela E. Scheuerle; Emma J. Sanchez; et al. (BMC, 2020)
Abstract Background Prune belly syndrome (PBS) is a rare, multi-system congenital myopathy primarily affecting males that is poorly described genetically. Phenotypically, its morbidity spans from mild to lethal, however, all isolated PBS cases manifest three cardinal pathological features: 1) wrinkled flaccid ventral abdominal wall with skeletal muscle deficiency, 2) urinary tract dilation with poorly contractile smooth muscle, and 3) intra-abdominal undescended testes. Despite evidence for a genetic basis, previously reported PBS autosomal candidate genes only account for one consanguineous family and single cases. Methods We performed whole exome sequencing (WES) of two maternal adult half-brothers with syndromic PBS (PBS + Otopalatodigital spectrum disorder [OPDSD]) and two unrelated sporadic individuals with isolated PBS and further functionally validated the identified mutations. Results We identified three unreported hemizygous missense point mutations in the X-chromosome gene Filamin A (FLNA) (c.4952 C > T (p.A1448V), c.6727C > T (p.C2160R), c.5966 G > A (p.G2236E)) in two related cases and two unrelated sporadic individuals. Two of the three PBS mutations map to the highly regulatory, stretch-sensing Ig19-21 region of FLNA and enhance binding to intracellular tails of the transmembrane receptor β-integrin 1 (ITGβ1). Conclusions FLNA is a regulatory actin-crosslinking protein that functions in smooth muscle cells as a mechanosensing molecular scaffold, transmitting force signals from the actin-myosin motor units and cytoskeleton via binding partners to the extracellular matrix. This is the first evidence for an X-linked cause of PBS in multiple unrelated individuals and expands the phenotypic spectrum associated with FLNA in males surviving even into adulthood.